2021
DOI: 10.1111/oik.08443
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation promotes plant invasions and indirect negative interactions

Abstract: Numerous pressures influence the ecological capacity and health of drylands globally. Shrubs are often a critical component of these systems and can function positively as foundation species through facilitation of other species. Nonetheless, limited attention has been paid to the potential negative and indirect effects of shrubs. Here, we tested the hypothesis that plant facilitation can both accelerate the invasion process and amplify the negative effects of an invader on the native community. The invasive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…values of d were positive or negative), those interactions involved the facilitation of a C4 native ( C. truncata ) by the exotics. Other studies have found facilitation of exotic species by natives (Lucero et al 2019, Cavieres 2021, Lortie et al 2021), an outcome predicted to increase as resources increase (Northfield et al 2018), although there are fewer examples of exotic species facilitating natives (Alba et al 2019, Wainwright et al 2019). While our findings suggest the potential for exotic species to facilitate the establishment of a native species, they also highlight the need for caution in interpreting the outcome of species interactions in heterogeneous landscapes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…values of d were positive or negative), those interactions involved the facilitation of a C4 native ( C. truncata ) by the exotics. Other studies have found facilitation of exotic species by natives (Lucero et al 2019, Cavieres 2021, Lortie et al 2021), an outcome predicted to increase as resources increase (Northfield et al 2018), although there are fewer examples of exotic species facilitating natives (Alba et al 2019, Wainwright et al 2019). While our findings suggest the potential for exotic species to facilitate the establishment of a native species, they also highlight the need for caution in interpreting the outcome of species interactions in heterogeneous landscapes.…”
Section: Discussionmentioning
confidence: 98%
“…values of d were positive or negative), those interactions involved the facilitation of a C4 native (C. truncata) by the exotics. Other studies have found facilitation of exotic species by natives (Lucero et al 2019, Cavieres 2021, Lortie et al 2021, an outcome predicted to increase as resources increase (Northfield et al 2018), although there are fewer examples of exotic species facilitating natives (Alba et al 2019, Wainwright et al 2019.…”
Section: The Role Of Interspecific Interactions In Invasionsmentioning
confidence: 93%
“…Species that deeply depend on facilitation can find their abundance limited by the availability of the habitat provided by their nurse plants. That might be an important factor explaining why species that rely more on facilitation are more locally rare than those that rely less on facilitation, a worldwide pattern linking facilitation and plant species coexistence (Soliveres et al, 2015a, but see Lortie et al, 2021; Lucero et al, 2021 or Vega‐Álvarez et al, 2019) for particular cases in which facilitation favors abundant species.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at net effects, one invader can inhibit or facilitate another one ( Flory and Bauer, 2014 ; Kuebbing and Nuñez, 2016 ; Zhang et al, 2020 ). Likewise, the overall impact of multiple invaders on native biodiversity and soil functioning may result from facilitative (positive) interactions, whereby multiple species increase the magnitude of their combined effects as compared to their individual effect, or from competitive (negative) interactions, in which case the combined effects are weaker than a single-species effect ( Lortie et al, 2021 ). Interactions among multiple invaders can also be neutral, in which case their combined impact is negligible ( Kuebbing, 2014 ).…”
Section: Introductionmentioning
confidence: 99%